Binary Choices of Households about REDD Regime in Nepalese Forest - Raghu Bir Bista (Quantitative Economics and Management Studies, 2022)
This study studies empirically whether REDD is a better alternative to community forest of Nepal. The data set of the study is primary nature in which the primary data sets were collected from the household survey in the Kafle community forest of Lamatar-6, Lalitpur District, Nepal. The study has employed descriptive statistics and probit models to analyze the data sets. The study found 45 percent households depend on the community forest for livelihood materials (firewood, leaf litter, grass, water), along with Service and Agriculture income sources. As a result of binary choice, the study in mixed familiarity with REDD finds only 44 percent of households expect that REDD will be a better livelihood alternative to the poor. Further, 63 percent of households expect livelihood from REDD. Large household respondents don’t believe that REDD will be a better alternative livelihood for the poor. Almost all households expect REDD for livelihood objectives. From estimation, household stakeholders who have good asset holdings (land and livestock) think that REDD will be not a better livelihood alternative to the poor. However, the household stakeholders who have literacy, different food sufficiency level, landholding (1>), different earnings per day, Rsex, per day earning, and age thinks that REDD will be a better alternative. Thus, the poor households expect a livelihood role from REDD in Nepal. Therefore, REDD should be more beneficial to the poor household stakeholders and their livelihoods.